Energy consumption monitoring in a smart campus - Santos, Catarina Marinho Nogueira dos (2018)
The increase electricity consumption in developed countries, caused by a larger number of more powerful and diversified power-connected devices, creates consumption peaks, which lead to the need of integrating new ways to produce, distribute and consume energy with more efficiency. Also considering the constant increase in fuel prices, the threats of global warming, implications of carbon, among other emissions from traditional fuels, a growing interest in improving energy efficiency arose. In this dissertation we present a scalable prototype which can monitor energy, temperature and luminosity, showing real-time data and afterwards with the gather data, do more specific analysis, allowing for stakeholders to make better informed decisions, to work towards energy efficiency and sustainability. The developed prototype, which includes both hardware and software, is based on low cost IoT devices and LoRa network implementation, to create an appropriate and easily adapted system to any room in the university. We demonstrate the chosen devices and all the implementation done, and, also demonstrate the analysis done with the data gathered during the period of observation, in order to get energy efficiency measures. This approach towards building energy efficiency services, where context information from locally installed sensors, can be manipulated to identify consumption patterns and, later, implement actions in a service basis to save energy in a building. Usage of external information, like local maps, building materials, external weather conditions and room occupancy can be used to improve further saving actions.